Optical spectroscopy and emission properties of Ho3 +-doped gadolinium calcium silicoborate glasses for visible luminescent device applications - C. R. Kesavulu (2018)
© 2017 Elsevier B.V. The Ho3 +-doped gadolinium calcium silicoborate glasses with the composition of 25Gd2O3+ 10CaO + 10SiO2+ (55 − x)B2O3+ xHo2O3, where x = 0.0, 0.5, 1.0, 1.5, 2.0 and 2.5 mol%, were synthesized by well-known melt quenching method. These glasses have been characterized through physical, structural, optical, visible emission and decay curve analysis. From the absorption spectrum, Judd-Ofelt intensity parameters for 1.0 mol% Ho2O3doped glass have been carried out and were used to examine radiative properties for the important visible emitting levels of Ho3 +ions. The present Ho3 +:glasses show strong green emission at 545 nm and red emission at 655 nm under excitation at 452 nm. The radiative decay time and stimulated emission cross-section for the (5S2,5F4) →5I8transition are found to be 280 μs and 0.63 × 10− 20cm2, respectively. Decay curves for all the concentration of Ho3 +ions exhibit non-exponential nature for (5S2,5F4) →5I8transition. The decrease in decay times is due to the resonant energy transfer among the excited Ho3 +ions. Hence, these results confirm that the present silicoborate glass system could be considered as a promising candidate for visible green laser applications.